2020
DOI: 10.1002/chem.202000615
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Perturbation of Oncogenic Protein Folding: from the Prediction of Locally Unstable Structures to the Design of Disruptors of Hsp90–Client Interactions

Abstract: Veronesi, Marina et al. (2020) Chemical perturbation of oncogenic protein folding: from the prediction of locally unstable structures to the design of disruptors of Hsp90-Client interactions. Chemistry -A European Journal, 26 (43). pp. 9459-9465.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 52 publications
(20 reference statements)
0
31
0
Order By: Relevance
“…The nature of the electrostatic interactions between the adaptor (positive) and the substrate (negative) opens to the design of negatively charged compounds to optimize electrostatic complementarity and assess LZTR1 recruitment properties. 43 …”
Section: Discussionmentioning
confidence: 99%
“…The nature of the electrostatic interactions between the adaptor (positive) and the substrate (negative) opens to the design of negatively charged compounds to optimize electrostatic complementarity and assess LZTR1 recruitment properties. 43 …”
Section: Discussionmentioning
confidence: 99%
“…Paladino and co-workers explored this route, identifying locally unstable substructures in native structures of Hsp90 client proteins [33] (Figure 2B). Such unstable substructures are indeed located in protein regions that have a high probability to unfold locally and exhibit conformational heterogeneity; however, they do not necessarily coincide with intrinsically disordered regions or unstructured loops.…”
Section: Interfering With the Chaperone Machinery: Targeting Hsp90 To Block Protein Foldingmentioning
confidence: 99%
“…The recent series of studies by Colombo and colleague have reported results of computer-aided design and synthesis of new allosteric ligands with micromolar to nanomolar anticancer activities, demonstrating the power of computational approaches in discovering allosteric modulators that can probe the relationships between structure dynamics and function of the Hsp90 proteins and regulatory complexes with client proteins (Sattin et al, 2015 ; D'Annessa et al, 2017 ; Masgras et al, 2017 ; Ferraro et al, 2019 ; Hu et al, 2020 ; Sanchez-Martin et al, 2020 ). Computational targeting of the Hsp90 client proteins based on the prediction of locally unstable substructures in proteins was used to develop potent probes and peptides blocking Hsp90-client interactions (Colombo et al, 2020 ). Recent efforts have also produced small molecules that can inhibit the inter-chaperone protein-protein interactions for Hsp70 chaperone (Gestwicki and Shao, 2019 ).…”
Section: Exploiting Allosteric Mechanisms and Cryptic Binding Sites Fmentioning
confidence: 99%